STRENGTHENING CHARACTER VALUES THROUGH CO-CURRICULAR ACTIVITIES AT STATE MIDDLE SCHOOL 2 GORONTALO - Fahmid Abdullah; Lucyane Djaafar; Ramli Mahmud (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Character development among students remains a challenge in schools because participation in various educational activities does not always result in the expected behavioral changes. Research on co-curricular activities generally focuses on the character traits that are formed, while explanations regarding the process of character formation and the factors determining its success remain limited. This study aims to analyze the process of character strengthening through co-curricular activities and to identify the factors influencing their effectiveness at SMP Negeri 2 Gorontalo. The study employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and were analyzed through data condensation, data presentation, and the drawing and verification of conclusions. The results indicate that responsibility, cooperation, and tolerance are not formed instantly through students’ participation in activities, but rather through repeated social experiences involving role-sharing, negotiation, conflict resolution, and joint decision-making. The effectiveness of this process is influenced by the interconnection between school commitment, teacher role modeling, the quality of student participation, and school culture. These findings suggest that the quality of student engagement is a more decisive factor in character development than the mere existence of co-curricular programs; therefore, character education must be understood as a dynamic social process that unfolds within daily learning experiences